Les mobilités domicile-travail dans les réseaux d’agglomérations - Julien Gingembre; John Baude (EchoGéo)
Spatial distortion between the home and the workplace has increased commuting flows between urban areas. The mobility networks thus formed result not only in creating links between regional metropolitan areas and their satellite urban cores, but also in developing flows between greater urban areas or between smaller urban cores. The networks more or less fit the contours of the major metropolitan hubs. Executives are the most overrepresented in home to work commuting flows. An econometric analysis from census data shows that their sensitivity to distance is the lowest among socio-professional groups and that although their sensitivity to the size of the job market is null, the latter does determine their number commuting between greater urban areas.